Morphological and Genomic Differences Between Cutting and Racing Lines of Quarter Horses - Meira, Camila Tângari [UNESP]; Curi, Rogerio Abdallah [UNESP]; Silva, Josineudson Augusto II Vasconcelos [UNESP]; Monteiro Corrêa, Marcio José [UNESP]; Nunes de Oliveira, Henrique [UNESP]; Silveira da Mota, Marcilio Dias [UNESP] (My University, 2013)
To investigate morphological and genomic differences between cutting and racing lines of Quarter Horses, 120 racing and 68 cutting animals of both sexes, registered at the Brazilian Association of Quarter Horse Breeders, were used. Blood samples were collected, and the following physical traits were measured: weight; height at withers; body length; length of the shank, pastern, rump, head, and neck; and chest, shank, and hoof circumference. For analysis of genomic differences, 54,602 single-nucleotide polymorphisms (SNPs) were genotyped using the Equine SNP50 BeadChip, and the quality of individual and SNP genotype data were evaluated. The fixation index, FST, was used to identify genome regions that were altered in the lines by selection. The results showed significant differences between the lines in all physical traits. Quality control led to the exclusion of four cutting animals with a call rate of <0.95. After filtering, 12,544, 13,815, and 13,370 SNPs were excluded for the whole population (n = 184), the 120 racing animals, and the 64 cutting animals, respectively. The number of informative polymorphisms detected in each line and in the whole population indicated that the Equine SNP50 BeadChip can be used in genetic studies of Quarter Horses. The fixation index, FST, identified 2,558 genome regions that may have been modified by divergent selection. © 2013 Elsevier Inc.
Keywords: Genome-wide association study; Horse; Physical traits; SNPs; Animalia; Equidae